Cover Feature: Synthesis and Physicochemical Properties of Ruthenium(II) Complexes Having Pentadentate Scaffolds: Water Oxidation Activity and Deactivation Pathway (Eur. J. Inorg. Chem. 2/2019). Issue 2 (8th January 2019) - Kundu, Animesh; Khan, Srimoyee; Dey, Subhasis; Dutta, Chiranjit; Anoop, Anakuthil; Mandal, Sukanta
Abstract : The Cover Feature shows an aqua‐coordinated mononuclear ruthenium complex with a pentadentate ligand scaffold exhibiting oxidation of water, using cerium(IV) as sacrificial electron acceptor at pH 1. The picture also highlights an initial side reaction involving oxidative N‐debenzylation, which leads to deactivation of the catalyst. More information can be found in the Full Paper by S. Mandal et al.